Congenital dermal sinus of the cervical spine in an adult - DAĞÇINAR, ADNAN (CHURCHILL LIVINGSTONE, 2008)
Congenital dermal sinuses are epithelium-lined tracts that extend from an opening in the skin through deeper tissues. Most dorsal congenital dermal sinuses are located in the lumbosacral area; a cervical location is unusual. This report describes a 24-year-old woman who presented with neck pain of 6 months' duration. A dimple in the skin over her cervical spine and a stunted right foot (0.5 cm shorter than the left) were detected on physical assessment. Neurological examination revealed increased deep tendon reflexes in her lower extremities. Magnetic resonance imaging showed a dermal sinus extending from the dimple site to the spinal cord near the C4-C5 vertebrae. Laminectomies were performed at C3-C4 and the tract was totally excised. The patient's neck pain completely resolved and her deep tendon reflexes were normal at 12 months after surgery. Tethered spinal cord alone does not necessarily demand surgery; however, if a congenital dermal sinus is present then surgery is indicated to prevent spinal infection. Even if there are no neurological symptoms, the tract must be surgically removed and the cord must be fully released to prevent future infectious or neurological complications. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: adulthood; dermal sinus tract; tethered cord; CORD SYNDROME; MYELOPATHY; ABSCESS; LESIONS; TRACTS; CYST